Pragmática y argumentación en el discurso publicitario. El caso de la campaña de SanCor Bio en Argentina. - Fazio, María Eugenia (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2009)
This paper analyzes the advertising campaign of SanCor Bio milk with L.casei and natural fructanos, which was disclosed in Argentina through an Internet site and two television advertisements. The tools used for the analysis are mainly taken from pragmatic and artistotelic rhetoric, among other argumentation theories, Audiences, speakers, message building strategies and advertising goals are identified. Chain arguments of the advertisements are analyzed, specially the way in which scientific terms and technology institutions are used as sale strategies.